Two Concepts of a Lie: Václav Havel on Living in a Communist regime - Krása, Ondřej (My University, 2022)
According to Václav Havel’s famous essay "The Power of powerless" life within a lie is at the core of the communist regime in Czechoslovakia. Life within a lie is characteristic for the great majority of people and is contrasted with life within the truth which is characteristic of dissent movement. In this paper, I will try to shed some light on the concept of “living within a lie.” I will show that Havel develops not one but two concepts of a lie: on the one hand, lie is deliberate pretence; on the other hand, lie is seduction by consumerist values. The first meaning of a lie is derived from Havel’s analysis of the specifics of the Soviet sphere of influence, namely central role of ideology with omnipresent demands on public support of the regime. The second meaning of a lie is heavily influenced by a critical assessment of modern society from the leading figure of the Czech underground movement Ivan Jirous and leading Czech philosopher Jan Patočka. This double meaning of a lie enables Havel to capture both specific problems of living under the communist regime and general problems of living in modern society anywhere in the world. In the final chapters of this paper, I will show that Havel is not clear about how these two meanings of a lie are connected and that there are problems resulting from these unclarities both for Havel’s analysis of the communism and his proposed solution of the crisis.
Dva pojmy lži: Život v komunismu podle Václava Havla
Keywords: Václav Havel; truth; lie; dissent; Jan Patočka; underground; communism; Václav Havel; pravda; lež; disent; Jan Patočka; underground; komunismus